2020
DOI: 10.1007/s12603-020-1501-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the COVID-19 Epidemic on Physical Activity in Community-Dwelling Older Adults in Japan: A Cross-Sectional Online Survey

Abstract: Objectives The objective of this study was to investigate changes in physical activity (PA) between January (before the COVID-19 epidemic) and April (during the COVID-19 epidemic) 2020 in community-dwelling older adults in Japan. Design Cross-sectional online survey. Setting and Subjects From April 23 to 27, 2020, an online survey was completed by 1,600 community-dwelling older adults in Japan. Methods We assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
165
4
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 250 publications
(195 citation statements)
references
References 11 publications
13
165
4
3
Order By: Relevance
“…PA has been previously described as a risk factor for frailty [ 8 , 9 , 10 ] and a key component of interventions to prevent or reduce the development and progression of frailty [ 3 , 11 , 12 , 13 ]. It has been estimated that the preventive measures applied during the COVID-19 pandemic led to a 25% reduction of PA in the general population [ 6 , 14 , 15 , 16 , 17 ], and more than 45% in older adults [ 6 , 14 , 15 , 16 , 18 , 19 ]. Despite these data, the possible determinants of this reduction in PA levels have not been explored yet.…”
Section: Introductionmentioning
confidence: 99%
“…PA has been previously described as a risk factor for frailty [ 8 , 9 , 10 ] and a key component of interventions to prevent or reduce the development and progression of frailty [ 3 , 11 , 12 , 13 ]. It has been estimated that the preventive measures applied during the COVID-19 pandemic led to a 25% reduction of PA in the general population [ 6 , 14 , 15 , 16 , 17 ], and more than 45% in older adults [ 6 , 14 , 15 , 16 , 18 , 19 ]. Despite these data, the possible determinants of this reduction in PA levels have not been explored yet.…”
Section: Introductionmentioning
confidence: 99%
“…The restrictions during COVID-19 have also led to concerns around the impact on PA particularly among vulnerable groups. Indeed, evidence suggests that PA in older adults has significantly decreased during COVID-19, with concerns that this may lead to increased risk of decline and disability ( Roschel et al , 2020 ; Yamada et al ., 2020 ). Emerging evidence also suggests that the decline may be more prevalent in existing ‘at risk’ groups, particularly those not meeting current PA guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Yamada et al . reported that the time spent doing physical activity significantly decreased as a result of the COVID‐19 pandemic affecting older adults in Japan 14 . For healthy older adults and older adults with frailty, muscular weakness is decreased by physical activity, ranging from low intensity walking to more vigorous sports and resistance exercise 15 .…”
Section: Discussionmentioning
confidence: 99%